Pengaruh Kesiapan Belajar, Kemampuan Teknologi, dan Motivasi Berprestasi terhadap Keaktifan Belajar Mahasiswa Fhisip UT Makassar dengan Self-Efikasi sebagai Variabel Moderasi - Alwi, Muh.; Kusmaladewi Kusmaladewi; Risnashari Risnashari; Juhardi Juhardi; Sitti Wahidah Masnani (Institut Nalanda, 2026)
Online learning has become one of the innovations in modern education, enabling students to access learning materials and participate in instructional interactions flexibly without being limited by space and time, as reflected in the learning characteristics of Universitas Terbuka (UT). Tutorial Tatap Maya (TUWEB) is designed as a communication medium between students and tutors to support the learning process, broaden knowledge, deepen subject matter, and clarify students’ understanding of the courses they study. Based on this background, this study aims to analyze the effect of learning readiness, technological ability, and achievement motivation on UT students’ learning activity by involving self-efficacy as a moderating variable. This study employed a quantitative approach. The sample size was determined using probability sampling with Harry King’s Nomogram formula at a 5% error level and a 95% multiple factor of 1.195, resulting in a total sample of 200 respondents. Data were collected using a questionnaire with a 1–4 Likert scale and analyzed with the assistance of SmartPLS software. The results showed that technological ability influenced learning activity, with an f-square value of 0.124, categorized as a small to moderate effect. Learning readiness also had a significant effect on learning activity, with an f-square value of 0.058, indicating a small effect. Achievement motivation did not significantly affect learning activity, as shown by an f-square value of 0.000. Self-efficacy had a significant effect on learning activity, with an f-square value of 0.154, categorized as a moderate effect. However, self-efficacy did not moderate the relationship between technological ability, learning readiness, or achievement motivation and students’ learning activity.